Amelioration of Functional, Metabolic, and Morphological Deterioration in the Retina following Retinal Detachment by Green Tea Extract - Kai On Chu; Yolanda Wong Ying Yip; Kwok Ping Chan; Chi Chiu Wang; Danny Siu Chun Ng; Chi Pui Pang (MDPI AG, 2024)
Retinal detachment (RD) can result in the loss of photoreceptors that cause vision impairment and potential blindness. This study explores the protective effects of the oral administration of green tea extract (GTE) in a rat model of RD. Various doses of GTE or epigallocatechin gallate (EGCG), the most active ingredient in green tea catechins, were administered to Sprague Dawley (SD) rats with experimentally induced retinal detachment. The rats received sub-retinal injections of hyaluronic acid (0.1%) to induce RD and were given different doses of GTE and EGCG twice daily for three days. Notably, a low dose of GTE (142.9 mg/kg) caused significantly higher signal amplitudes in electroretinograms (ERGs) compared to higher GTE doses and any doses of EGCG. After administration of a low dose of GTE, the outer nuclear layer thickness, following normalization, of the detached retina reduced to 82.4 ± 8.2% (Mean ± SEM, p < 0.05) of the thickness by RD treatment. This thickness was similar to non-RD conditions, at 83.5 ± 4.7% (Mean ± SEM) of the thickness following RD treatment. In addition, the number of TUNEL-positive cells decreased from 76.7 ± 7.4 to 4.7 ± 1.02 (Mean ± SEM, p < 0.0001). This reduction was associated with the inhibition of apoptosis through decreased sphingomyelin levels and mitigation of oxidative stress shown by a lowered protein carbonyl level, which may involve suppression of HIF-1α pathways. Furthermore, GTE showed anti-inflammatory effects by reducing inflammatory cytokines and increasing resolving cytokines. In conclusion, low-dose GTE, but not EGCG, significantly alleviated RD-induced apoptosis, oxidative stress, inflammation, and energy insufficiency within a short period and without affecting energy metabolism. These findings suggest the potential of low-dose GTE as a protective agent for the retina in RD.